A modern approach to ERCP: maintaining efficacy while optimising safety. (17th April 2016) - Nalankilli, Kumanan; Kannuthurai, Sutharshan; Moss, Alan
Abstract : Background and Aim: Endoscopic retrograde cholangiopancreatography (ERCP) is technically challenging and complications such as post‐ERCP pancreatitis (PEP) remain a concern. Modern ERCP techniques aim to maintain efficacy and improve safety. There are limited data regarding efficacy and safety of ERCP carried out by a newly qualified practitioner using modern techniques. The aim of the present study was to conduct an ERCP practice audit and compare it with an Australian national survey in order to review the evidence base underlying modern ERCP practice. Methods: All ERCP carried out by a newly qualified practitioner, using prospectively collected data, from September 2011 to May 2015, were audited. Outcomes were compared to an Australia‐wide survey of ERCP practice. A literature review was carried out regarding recent developments in ERCP practice. Results: Audit results correlated well with national data. All 478 ERCP were therapeutic and had pre‐procedure imaging. Wire‐guided biliary cannulation was used. Success rate was 97%. Overall adverse‐event rate was 0.8%. Choledocholithiasis was the predominant indication (72%). Biliary cannulation was successful in 338 of 348 naiive papillae. Of these, there were 53 (16%) difficult cannulations but the needle‐knife sphincterotomy (NKS) rate was low compared to national data (13% vs 33%). Rate of dual‐wire cannulation technique was higher (87% vs 30%). Pancreatic duct stenting (done in 32 cases [70% of dual‐wire cannulation cases]) and rectal indomethacin (25%) were used to reduce PEP risk. Conclusions: A newly qualified ERCP proceduralist achieved high success rates with minimal adverse events using modern techniques. Practice was consistent with national data, although dual‐wire cannulation technique was preferred to NKS. Evidence base for modern ERCP techniques was reviewed. ERCP efficacy and safety should be monitored by practice audit.